2021
DOI: 10.1111/aas.13982
|View full text |Cite
|
Sign up to set email alerts
|

Chronic dysglycemia and risk of SARS‐CoV‐2 associated respiratory failure in hospitalized patients

Abstract: Background Diabetes is common among patients with severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2)‐induced respiratory failure. We aimed to investigate the relationship between different stages of chronic dysglycemia and development of respiratory failure in hospitalized SARS‐CoV‐2 positive patients. Methods In this retrospective observational study, we included 385 hospitalized SARS‐CoV‐2 positive patients at Karolinska University Hospital, Sweden with an H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
(53 reference statements)
0
2
0
Order By: Relevance
“…In addition to the above speculations about SARS-CoV-2 as a cause of dysglycaemia, there is also evidence suggesting that patients with pre-existing dysglycaemia are prone to a more severe course of COVID-19. For example, some studies have shown that hospitalised SARS-CoV-2 positive with pre-diabetes, unknown diabetes and known poorly controlled diabetes are at increased risk of SARS-CoV-2-associated respiratory failure requiring intensive care 17. A higher burden of comorbidities, hyperglycaemia per se and chronic low-grade inflammation in diabetes may explain this observation 18…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the above speculations about SARS-CoV-2 as a cause of dysglycaemia, there is also evidence suggesting that patients with pre-existing dysglycaemia are prone to a more severe course of COVID-19. For example, some studies have shown that hospitalised SARS-CoV-2 positive with pre-diabetes, unknown diabetes and known poorly controlled diabetes are at increased risk of SARS-CoV-2-associated respiratory failure requiring intensive care 17. A higher burden of comorbidities, hyperglycaemia per se and chronic low-grade inflammation in diabetes may explain this observation 18…”
Section: Discussionmentioning
confidence: 99%
“…For example, some studies have shown that hospitalised SARS-CoV-2 positive with pre-diabetes, unknown diabetes and known poorly controlled diabetes are at increased risk of SARS-CoV-2-associated respiratory failure requiring intensive care. 17 A higher burden of comorbidities, hyperglycaemia per se and chronic low-grade inflammation in diabetes may explain this observation. 18 Open access et al identifiy fasting glucose as an independent predictor for 28-day mortality in hospitalised individuals with COVID-19 and previously unknown diabetes.…”
Section: Relationship With Previous Studiesmentioning
confidence: 99%